Enhancing Elementary Students' Academic Achievement Through the Scramble Learning Model - Nugraha, Ferry Ichsan; Nugraha Permana Putra; Hema WIdiawati (Journal of Innovation and Research in Primary Education, 2025)
Traditional lecture-based teaching methods in Indonesian elementary schools often result in passive learning environments and suboptimal academic achievement, particularly in integrated subjects requiring cultural understanding. The scramble learning model, an interactive game-based approach involving the arrangement of scrambled words and sentences, has emerged as a promising pedagogical strategy to enhance student engagement and learning outcomes. This study investigated the effect of the scramble learning model on academic achievement among fourth-grade students learning the theme "Indonesia's Rich Culture" at SDN 1 Jamblang, Cirebon Regency. A pre-experimental design with one-group pretest-posttest configuration was employed. All 32 fourth-grade students participated in the study. Data were collected using a validated 20-item multiple-choice achievement test administered before and after the scramble model intervention. Statistical analysis included Shapiro-Wilk normality testing, Wilcoxon Signed-Rank test for hypothesis testing, and normalized gain (N-Gain) calculation to assess effect size.  Student academic achievement improved significantly from a pretest mean of 56.25 to a posttest mean of 87.5. The Wilcoxon test revealed a statistically significant difference (p = 0.000 < 0.05), with all 32 students showing positive performance gains. The N-Gain score of 0.78 indicated high effectiveness according to Hake's classification. The percentage of students achieving minimum competency criteria increased from 31.25% to 75%. The scramble learning model significantly enhances academic achievement in elementary cultural education. The universal improvement across all participants demonstrates the model's effectiveness in transforming passive learning environments into active, engaging educational experiences. These findings support the implementation of interactive, game-based learning strategies in Indonesian elementary schools to improve student outcomes in integrated thematic curricula.